PRODUÇÃO DE ARROZ NAS MICRORREGIÕES DO RIO GRANDE DO SUL: EVOLUÇÃO, ESPECIALIZAÇÃO E CONCENTRAÇÃO - Janaina Ottonelli (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
Brazil is the country with the highest rice production outside Asia. The Brazilian State of Rio Grande do Sul is responsible for two-thirds of all domestic production. This study questions whether the regions with the highest production of rice are economically specialized in the product. Therefore, we aim to characterize the evolution of cultivation from 1990 to recent years, identify the micro-regions of the Rio Grande do Sul State specialized in rice production, and verify the degree of concentration of production over time. The methodology describes the evolution of productivity, harvested area and quantity produced; the measure of the locational quotient (QL) to identify the specialized regions; and the measure of the locational Gini index (GL) to check the degree of concentration of rice production. The results indicate an increase in the number of specialized regions in rice production, but a reduction in the spatial concentration.